The Role of Forgiveness in Post-Traumatic Growth: A Cross-Sectional Study of Emerging Adults with Adverse Childhood Experiences - Anindhita Parasdyapawitra Amaranggani; Kartika Sari Dewi (International Journal Labs, 2022)
Adverse Childhood Experiences (ACEs) are associated with various negative impacts on the mental health of emerging adults. Previous studies have shown that post-traumatic personal growth after a particularly challenging event can be facilitated by the adoption of emotional coping strategies, such as forgiveness. This study examines the relationship between forgiveness and post-traumatic growth among emerging adults with ACEs in Indonesia. The sample consisted of 152 emerging adults, aged 18-25 years (M = 21.53; SD = 1.919), mostly female (92.1%), and reported at least one ACEs during their childhood. The instruments in this study were the WHO ACE-International Questionnaire, Post-traumatic Growth Inventory (21 items, α= 0.922) and the Forgiveness Scale (34 items, α = 0.935). Analysis was performed using Spearman's rho. The results of the study revealed that forgiveness was positively and significantly correlated with post-traumatic growth (rxy .471, p= .000). The originality of this study revealed that the three dimensions of forgiveness are strongly related to post-traumatic personal growth in ACEs survivors. This article expands the discussion on the inconsistency of the role of the forgiveness dimension towards others. Based on these results, the development of a forgiveness-based intervention to enhance post-traumatic personal growth for ACE survivors is proposed